Rancang Bangun Website Project Management Untuk Project Specific Repository Checklist Pt Anabatic Digital Raya Menggunakan Metode Rad (Rapid Application Development) - Ade Lita; Syahrizal Dwi Putra (Jurnal Manajamen Informatika Jayakarta, 2022)
The development of the digital era is currently progressing very rapidly. Website-based applications can be a solution needed by companies that want to develop a more integrated online communication and information system. PT Anabatic Digital Raya is improving the efficiency and effectiveness of the Compliance Officer (CO) team in the process of checking project documents. By building a project management website application for the Project Specific Repository Checklist file by applying the RAD (Rapid Application Development) method, the goal to be realized will be achieved, namely increasing the efficiency and effectiveness of the Compliance Officer team.